PERBAIKAN SIFAT FUNGSIONAL TEKNIS TEPUNG BIJI KELOR (MORINGA OLEIFERA) DENGAN PERKECAMBAHAN - Candytias Puspitasari; Sukarno Sukarno; Slamet Budijanto (Jurnal Teknologi dan Industri Pangan, 2019)
Germination constitutes one of bio-processing techniques and has attracted a tremendous attention due to its advantageous effects on the improvement of technical functional properties of grains. Mean-while, blanching has been used as the complementary treatment in germination. The aim of this study was to evaluate the changes in the functional properties of Moringa oleifera seed flour due to germination and blanching that affect the characteristics of the resulting food the products. Germination was performed at four levels of incubation time (0, 48, 72, and 96 hours) at room temperature in the dark room and two levels of blanching time (0 and 30 second). The functional properties analyzed consisted of bulk density, flour solubility, water and oil absorption, and capacity and stability of emulsion. The results of this study showed that germinated Moringa seed flour had significantly better technical functional characteristics than the ungerminated ones, i.e. bulk density (0.33-0.43 g/mL), flour solubility (16.82-21.00 g/g), water absorp-tion capacity (0.93-0.99 g water/g), oil absorption capacity (1.18-1.58 mL oil/g), and emulsion capacity (88.80-91.70%). Blanching decreased the functional properties of the flour. The statistical analysis showed that there was no significant interaction between two factors in all parameters. This study shows that ger-mination is a good method to improve the functional properties of Moringa seed flour, but blanching dec-reases them. Germination without blanching is recommended to improve the technical functional charac-teristics of the flour.